Developing a Taxonomy To Understand and Measure Outcomes of Success in Community-Based Elder Mistreatment Interventions, New York City, New York, 2018-2019 - Lachs, Mark ([Verlag nicht ermittelbar], 2022)
Research tools available to help advance knowledge of effective community-based elder mistreatment (EM) interventions are limited. The field lacks an understanding of what success means in EM response program (EMRP) interventions, which work directly with victims to reduce the risk of re-victimization. Without establishing indicators of EMRP success, it is not possible to develop valid intervention outcome measures to compare different EMRP models toward the development of evidence-based practice. Informed by the EMRP practice principle of older adult self-determination, this study developed a victim-centric taxonomy of case outcomes that indicate EMRP success. This study drew on two sources of data, including interviews with EM victims and a scoping review to inform taxonomy development. Prioritizing the perspective of victims, this study conducted interviews with 27 victims involved in EMRP services who vary in EM subtype, gender, and race/ethnicity. The taxonomy of successful EMRP outcomes will serve as important research infrastructure to support the development of EMRP intervention outcome measurement in future research.